Encapsulating Cas9 into extracellular vesicles by protein myristoylation. Issue 4 (5th April 2022) - Whitley, Joseph Andrew; Kim, Sungjin; Lou, Lei; Ye, Chenming; Alsaidan, Omar Awad; Sulejmani, Essilvo; Cai, Jingwen; Desrochers, Ellison Gerona; Beharry, Zanna; Rickman, Catherine Bowes; Klingeborn, Mikael; Liu, Yutao; et al.
Abstract: CRISPR/Cas9 genome editing is a very promising avenue for the treatment of a variety of genetic diseases. However, it is still very challenging to encapsulate CRISPR/Cas9 machinery for delivery. Protein N‐myristoylation is an irreversible co/post‐translational modification that results in the covalent attachment of the myristoyl‐group to the N‐terminus of a target protein. It serves as an anchor for a protein to associate with the cell membrane and determines its intracellular trafficking and activity. Extracellular vesicles (EVs) are secreted vesicles that mediate cell‐cell communication. In this study, we demonstrate that myristoylated proteins were preferentially encapsulated into EVs. The octapeptide derived from the leading sequence of the N‐terminus of Src kinase was a favourable substrate for N‐myristoyltransferase 1, the enzyme that catalyzes myristoylation. The fusion of the octapeptide onto the N‐terminus of Cas9 promoted the myristoylation and encapsulation of Cas9 into EVs. Encapsulation of Cas9 and sgRNA‐eGFP inside EVs was confirmed using protease digestion assays. Additionally, to increase the transfection potential, VSV‐G was introduced into the EVs. The encapsulated Cas9 in EVs accounted for 0.7% of total EV protein. Importantly, the EVs coated with VSV‐G encapsulating Cas9/sgRNA‐eGFP showed up to 42% eGFP knock out efficiency with limited off‐target effects in recipient cells. Our study provides a novel approach to encapsulate CRISPR/Cas9 protein and sgRNA into EVs. This strategy may open an effective avenue to utilize EVs as vehicles to deliver CRISPR/Cas9 for genome‐editing‐based gene therapy.